C.B. Macpherson: Dilemmas of Liberalism and Socialism - Clement, Wallace (Labour / Le Travail, 1991)
The article reviews the book, "C.B. Macpherson: Dilemmas of Liberalism and Socialism," by William Leiss.
Keywords: BOOKS -- Reviews; LEHRER, Susan; Labor policy; Nonfiction; ORIGINS of Protective Labor Legislation for Women, 1905-1925 (Book)